2022
DOI: 10.1101/2022.01.19.476033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined multiple transcriptional repression mechanisms generate ultrasensitivity and oscillations

Abstract: Transcriptional repression can occur via various mechanisms, such as blocking, sequestration, and displacement. For instance, the repressors can hold the activators to prevent binding with DNA or can bind to the DNA-bound activators to block their transcriptional activity. Although the transcription can be completely suppressed with a single mechanism, multiple repression mechanisms are utilized together to inhibit transcriptional activators in many systems, such as circadian clocks and NF-κB oscillators. This… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…Indeed, measurements have shown that fast cell cycle oscillations persist after the first cell cycle despite the fact that (cyclin B, active Cdk1) bistability is absent Tsai et al (2014). Recent work on circadian clocks and NF-κB oscillators driven by a transcriptional negative feedback loop also showed that combinations of multiple (potentially redundant) repression mechanisms are used to generate strong oscillations (sharper responses) Jeong et al (2022). Our results are consistent with those findings and they are also in line with our previous work on combining multiple different functional motifs De Boeck et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, measurements have shown that fast cell cycle oscillations persist after the first cell cycle despite the fact that (cyclin B, active Cdk1) bistability is absent Tsai et al (2014). Recent work on circadian clocks and NF-κB oscillators driven by a transcriptional negative feedback loop also showed that combinations of multiple (potentially redundant) repression mechanisms are used to generate strong oscillations (sharper responses) Jeong et al (2022). Our results are consistent with those findings and they are also in line with our previous work on combining multiple different functional motifs De Boeck et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Burckard et al [20] provide new results on the synchronization of peripheral circadian clocks by intercellular communication between two cells or in small clusters of cells. In the final contribution, Jeong et al [21] investigate the role of multiple modes of transcriptional repression in generating many of these rhythms. By modelling three mechanisms of transcriptional repression—repressor R may bind to activator A on promoter P to block transcription (R:A:P is transcriptionally inactive), R binding to A may displace A from the promoter (R + A:P → R:A:P → R:A + P) and R binding to A may sequester A from P (R:A prevents A from binding to P)—they show that synergistic interactions of the three modes generate ultrasensitive transcriptional responses and robust oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Burckard et al [3] provided new results on the synchronization of peripheral circadian clocks by intercellular communication between two cells or in small clusters of cells. And Jeong et al [4] investigated the role of multiple modes of transcriptional repression in generating many of these rhythms.…”
Section: Introductionmentioning
confidence: 99%